Weighted regularity estimates for a class of higher-order nonlinear parabolic and elliptic systems. (March 2019) - Bui, The Anh; Duong, Xuan Thinh; Le, Xuan Truong
Abstract: In this paper, we prove the weighted L p regularity estimates and the Morrey regularity estimates for a class of higher-order nonlinear parabolic systems which satisfy an asymptotically regular condition. As a byproduct, similar regularity estimates are also obtained for a corresponding class of higher-order nonlinear elliptic systems.